Parâmetros sanguíneos e histologia hepática de frangos de corte suplementados com dietas contendo óleos essenciais - Vanessa Kelly Ferreira do Rosário Santos (2017)
The use of antibiotics for bird performance enhancement is a practice that aims at improving bird performance and promoting intestinal health. However, the widespread and inadequate use of such antibiotics has contributed to the emergence of resistant microorganisms becoming a public health problem in the world, leading to the need for further research on new products that can bring the same benefits on birds. Essential oils are investigated as potential products with good performance in performance enhancement. Nonetheless, there are only a few studies that evaluate the toxicity and changes that these substances can cause on birds. The objective of this study was to evaluate the hematological profile, liver function and liver histopathological analysis of broilers fed with portions containing microencapsulated essential oils extracted from Lemongrass (Cymbopogon flexuosus) and Pedestrian Tea (Lippia rotundifolia). One hundred and five day-old Cobb-type chicks housed in 30 cages by a completely randomized design were used in five treatments with three replicates of 10 animals. The treatments consisted of T1- control diet without performance improvement; T2- control diet containing conventional performance enhancers; T3- lemon-grass essential oil-based diet replacing conventional performance enhancers; T4- Pedestrian tea essential oil-based diet replacing the conventional performance enhancers and T5- Lemon grass essential oil and essential oil of pedestrian tea in lieu of conventional performance enhancers. At 42 days, the birds were euthanized and blood was collected for blood counts and serum biochemistry and the liver was evaluated for histopathological parameters. The parameters related to the blood counts indicated lower values in mean corpuscular volume and mean corpuscular hemoglobin in the group that received diet without performance improvement. In this same group of birds, the mean values of heterophiles were higher than in the other groups. The mean values observed for the gamma glutamyl transpeptidase enzyme in the group that received lemon grass oil feed were higher than those observed in the other treatments. The gender effect on the values of aspartate aminotransferase, albumin and glucose was observed. Wound characteristics from lipidosis, bile duct hyperplasia, and fibroplasia were observed in groups of birds that received a diet containing essential oils in variable scores, being higher in the group of birds that received a diet containing tea-pedestrian oil. In this study, the essential oils of microencapsulated lemon grass and pedestrian tea added to the diet did not cause changes in the hematological parameters of the birds. Changes in the levels of gammaglutamyl transferase enzymatic activity on birds fed with lemon grass essential oil were observed as well as higher scores of liver wounds characterized by lipidosis, bile duct hyperplasia, and fibroplasia with higher scores by birds fed with portions containing essential oils pedestrian tea.